The first experience of orthosis in deforming coxarthrosis - Andrukhova, Raisa; Boboshko, Ruslan; Nedilko Yurеy; Dondoreva, Irina; Pivovarov, Victor; Baev, Pavel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article contains results of an analysis of examinations of 42 patients with the hip joint pathology. Twelve of them revealed indications for orthosis, and ortheses were manufactured for the hip joint, hip and knee joints, and the whole leg. The above studies revealed a significant decrease in the pain syndrome expressiveness following the orthosis, an improvement of the patients’ functional capacities, the restoration of the function of statics and walking. Thus, orthosis can be an alternative method for treating patients with the hip joint pathology.